2014
DOI: 10.1186/1471-2229-14-112
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of sporamin expression in response to abiotic mechanical wounding and biotic herbivore attack in the sweet potato

Abstract: BackgroundPlants respond differently to mechanical wounding and herbivore attack, using distinct pathways for defense. The versatile sweet potato sporamin possesses multiple biological functions in response to stress. However, the regulation of sporamin gene expression that is activated upon mechanical damage or herbivore attack has not been well studied.ResultsBiochemical analysis revealed that different patterns of Reactive oxygen species (ROS) and antioxidant mechanism exist between mechanical wounding (MW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…Our previous work demonstrated that sporamin is induced by herbivory (Rajendran et al ., ). Sporamin, which has trypsin inhibitory activity (TPI), confers insect resistance on sweet potato (Yeh et al ., ,b).…”
Section: Resultsmentioning
confidence: 97%
“…Our previous work demonstrated that sporamin is induced by herbivory (Rajendran et al ., ). Sporamin, which has trypsin inhibitory activity (TPI), confers insect resistance on sweet potato (Yeh et al ., ,b).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, our wounding transcriptomic datasets [32] were carefully surveyed, and five bHLH transcription factors, namely IbbHLHa , b , c , d and e , were screened out. Subsequently, the gene expression pattern was monitored by qRT-PCR under a wounding time-course analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of plant biochemical variation in response to insect herbivory previously faced substantial limitations that have hindered the progress of the field. In particular, current practice in many labs is to use a single ecotype to measure differences between experimental treatments and to pool tissue from multiple leaves and individuals to obtain sufficient sample mass (War et al., ; Rajendran et al., ; Ferrieri et al., ). However, this approach has precluded the study of variation within and between individuals, which is what is relevant for real‐world interactions (Whitham, ; Winn, ; Bolnick et al., ).…”
Section: Discussionmentioning
confidence: 99%